Caracterización del germinado de Amaranto Caudatus (Amaranthus caudatus) - Rubio Gullqui, Andrea Carolina (2025)
Malnutrition remains a pressing issue in many vulnerable communities, particularly where access to nutrient-dense foods is limited. In this context, Amaranthus caudatus presents a promising alternative due to its rich nutritional composition. Its potential can be further augmented through germination, a biological process known to enhance nutrient bioavailability. This study aimed to evaluate the differences in physicochemical properties between germinated and non-germinated A. caudatus seeds, with the objective of maximizing their nutritional potential. Germination was carried out using three different substrates—moist absorbent paper, gauze, and cotton—under controlled conditions of humidity, temperature, and light. Standardized methodologies were employed for physicochemical analysis, and the resulting data were subjected to statistical evaluation using ANOVA to determine significant differences across treatments and substrates. The findings revealed a marked increase in moisture content (from 10.74% to 16.23%), ash (from 2.89% to 4.54%), protein (from 15.38% to 20.02%), and fiber (from 6.81% to 13.44%) in germinated seeds. Conversely, reductions were observed in fat content (from 6.51% to 3.38%) and starch (from 52.60% to 31.49%). Among the tested substrates, cotton proved to be the most effective, facilitating rapid and uniform germination. Overall, the germination process significantly enhances the nutritional attributes of A. caudatus, underscoring its potential as a valuable component in the development of functional foods and its suitability for future industrial applications.